2014
DOI: 10.11607/jomi.3413
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Single-Tooth Replacement: Dental Implant Versus Fixed Partial Denture

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…The reported studies compared cost effectiveness, advantages, and disadvantages of implant‐retained restorations and FPDs in the replacement of a tooth . These studies stated that in some cases, an FPD might be an appropriate choice, though implants have the advantage of preservation of sound teeth adjacent to the edentulous area . A comparison of patient subjective satisfaction levels between these two modalities has not yet been elaborated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported studies compared cost effectiveness, advantages, and disadvantages of implant‐retained restorations and FPDs in the replacement of a tooth . These studies stated that in some cases, an FPD might be an appropriate choice, though implants have the advantage of preservation of sound teeth adjacent to the edentulous area . A comparison of patient subjective satisfaction levels between these two modalities has not yet been elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Little research data have been reported on whether masticatory performance and patient perception is better with implant restorations or FPDs in unilateral posterior missing tooth conditions. Few studies comparing implants and FPDs as treatment options for single‐tooth replacement are available …”
mentioning
confidence: 99%
“…The results showed that implant‐supported single crowns had a 10.4% greater survival rate and cost on average US$261 more in a clinic setting and US$342 more in a hospital setting compared to fixed partial prostheses over a 10‐year period (Kim et al. ). That translated into a calculated cost‐effectiveness of US$25 in a clinic setting and US$33 in a hospital setting for each percent in 10‐year survival year gained.…”
Section: Cost‐effectiveness Of Replacing Single Missing Teethmentioning
confidence: 99%
“…The ultimate goal of the implant is meeting the patient's demand to replace one or more missing teeth beautifully, functionally, effectively and in a stable form [3].…”
Section: Introductionmentioning
confidence: 99%